Effects of Mechanical Insufflation-Exsufflation on Sputum Volume in Mechanically Ventilated Critically Ill Subjects. - Martínez-Alejos, Roberto; Martí, Joan-Daniel; Bassi, Gianluigi Li; Gonzalez-Anton, Daniel; Pilar-Diaz, Xabier; Reginault, Thomas; Wibart, Philippe; Ntoumenopoulos, George; Tronstad, Oystein; Gabarrus, Albert; Quinart, Alice; Torres, Antoni (Respiratory Care, 2021)
BACKGROUND: Mechanical insufflation-exsufflation (MI-E) is a noninvasive technique performed to simulate cough and remove sputum from proximal airways. To date, the effects of MI-E on critically ill patients on invasive mechanical ventilation are not fully elucidated. In this randomized crossover trial, we evaluated the efficacy and safety of MI-E combined to expiratory rib cage compressions (ERCC). METHODS: Twenty-six consecutive subjects who were sedated, intubated, and on mechanical ventilation > 48 h were randomized to perform 2 sessions of ERCC with or without additional MI-E before tracheal suctioning in a 24-h period. The primary outcome was sputum volume following each procedure. Secondary end points included effects on respiratory mechanics, hemodynamics, and safety. RESULTS: In comparison to ERCC alone, median (interquartile range) sputum volume cleared was significantly higher during ERCC+MI-E (0.42 [0--1.39] mL vs 2.29 [1--4.67] mL, P < .001). The mean ± SD respiratory compliance improved in both groups immediately after the treatment, with the greater improvement in the ERCC+MI-E group (54.7 ± 24.1 mL/cm H2O vs 73.7 ± 35.8 mL/cm H2O, P < .001). Differences between the groups were not significant (P = .057). Heart rate increased significantly in both groups immediately after each intervention (P < .05). Additionally, a significant increase in oxygenation was observed from baseline to 1 h post-intervention in the ERCC+MI-E group (P < .05). Finally, several transitory hemodynamic variations occurred during both interventions, but these were nonsignificant and were considered clinically irrelevant. CONCLUSIONS: In mechanically ventilated subjects, MI-E combined with ERCC increased the sputum volume cleared without causing clinically important hemodynamic changes or adverse events. (ClinicalTrials.gov registration: NCT03316079.)